Wind erosion enhanced by land use changes significantly reduces ecosystem carbon storage and carbon sequestration potentials in semiarid grasslands. (17th August 2018) - Li, Ping; Liu, Lingli; Wang, Jing; Wang, Zhenhua; Wang, Xin; Bai, Yongfei; Chen, Shiping
Abstract: Wind erosion exerts a fundamental influence on the biotic and abiotic processes associated with ecosystem carbon (C) cycle. However, how wind erosion under different land use scenarios will affect ecosystem C balance and its capacity for future C sequestration is poorly quantified. Here, we simulated different intensities of land uses in Inner Mongolia: control, 50% of vegetation mowed (50 M), 100% vegetation mowed (100 M), and tillage (TI). We monitored abiotic C flux caused by wind erosion, net ecosystem exchange (NEE), and soil characteristics from 2013 to 2016. We found that the frequency of heavy wind exerts a fundamental control over the severity of soil erosion, and its interaction with precipitation and vegetation characteristics explained 69% of the variation in erosion intensity. With increases in land use intensity, the abiotic C flux induced by wind erosion increased rapidly, equivalent to 33%, 86%, 111%, and 183% of the NEE of natural steppe in the control, 50 M, 100 M, and TI sites, respectively. The erosion‐induced decrease in fine fraction soils led to 31%, 43%, and 85% permanent losses of C sequestration potential in the surface soil for 50 M, 100 M, and TI sites. Overall, our study demonstrates that the abiotic C flux associated with wind erosion is too large to be ignored. The loss of C‐enriched fine particles not only reduces the current ecosystem C content but also results in an irreversible loss of future soil C sequestration potential. These dynamic soil characteristics need to be considered when projecting future ecosystem C balance in aeolian landscapes.